Study of Cultural and Tourism Industries Enabling Urban Renewal Around Animation and Comics - Sun, Aiguo (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, anime, games and derivative products have become increasingly popular in Japan and are loved and respected by more and more people. In the development of anime peripheral culture, anime theme parks, anime festivals, mascots and other derivative products, are also on the rise. Considering its great development prospect and potential commercial value, it is the remarkable propaganda and performance of the anime peripheral culture, and its development will have a greater impetus to the development of the anime peripheral culture, so the study of the peripheral area is of great significance. Taking Bengbu City as an example, we analyze its role in local economic development and conduct an in-depth study on the animation peripheral culture and local characteristic industries in the surrounding areas in order to promote the development of the city’s economy.